HUBUNGAN LINGKUNGAN SEKOLAH DENGAN MOTIVASI BELAJAR PESERTA DIDIK PADA MATA PELAJARAN ILMU PENGETAHUAN SOSIAL - Soni Harsono; Aminuyati Aminuyati; Thomy Sastra Atmaja (Universitas Tanjungpura, 2021)
ABSTRACTThe aims of this study was to determine the relationship between the schoolenvironment and students' learning motivation in social science subjects for classVIII SMP Islamiyah PTK. Descriptive quantitative method studies therelationship between variables X and Y. The data source is 11 students of classVIII questionnaire 32 items. The results of the research on the schoolenvironment, the percentage of the relationship between students and otherstudents (57.15%), the relationship between teachers and students (67.54%) anddiscipline (54.55%) concluded that the three indicators (59.75%) belonged to thecategory not good. The percentage of learning motivation results in rewards inlearning (56.07%), a conducive environment (65.46%) and a pleasantatmosphere (54.55%) the conclusions of the three indicators (58.70%) are in thepoor category. The relationship between the school environment and students'learning motivation in social science subjects for class VIII SMP Islamiyah PTKwas obtained tcount of 5,180, when compared with ttable of 5% with a significancelevel of 2.262, then tcount > ttable (5,180 > 2.262), then Hα was accepted. Themagnitude of the relationship between variables X and Y 0.865 is included in thevery strong category.Keywords: School environment and learning motivation